2013
DOI: 10.1002/j.2055-2335.2013.tb00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Dispensing Practices of General Practitioners and Community Pharmacists in Malaysia–A Pilot Study

Abstract: Background In Malaysia, general practitioners (GPs) in private clinics are legally permitted to dispense medicines. Aim To compare the dispensing practices of community pharmacists and GPs in private clinics. Method Simulated patients trained in common cold symptoms presented to GPs and community pharmacists in Penang, Malaysia. They observed their dispensing practices and recorded the number, category and cost of medicines dispensed and whether generic or brand name medicines were selected. Results Based on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Chong described the same Australian study in two papers . Alabid et al . described aspects of the same Malaysian study in three papers.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Chong described the same Australian study in two papers . Alabid et al . described aspects of the same Malaysian study in three papers.…”
Section: Resultsmentioning
confidence: 98%
“…Out of the 1107 papers in the original search and two added due to quoting the 2006 review, 148 papers met the criteria . Extraction of relevant papers from those found by the search strategy was done jointly by two researchers (IB and PN) and independently by a third researcher (AA).…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacists seemed to concede that accommodating customers’ demands is the only pragmatic choice for survival 37. The widespread nature of this practice in developing countries suggests an inherent systemic flaw in prevailing pharmacy legislations, particularly the lack of dispensing separation 19,21,24. The need to constantly exercise professional judgment and conscience before dispensing may also be detrimental to the pharmacists, resulting in a mental toll that affect their enthusiasm for the profession 38…”
Section: Discussionmentioning
confidence: 99%
“…11 In terms of disparity of drug pricing between community pharmacies and GPs, a recent study has revealed that there was a huge difference in pricing for common cold medicines between the two health care professionals. 13 Nevertheless, there was great gap between the community pharmacy and GPs toward the perception of current situation of intense competitive pharmaceutical price war, usage of generic medicines, and the disparities of medicine selling prices. In conjunction to the previous studies conducted with community pharmacists toward the issue of pharmaceutical price war, 5,14 this study aims to evaluate the perceptions of GPs toward issues of pharmaceutical price war, different bonus schemes provided by pharmaceutical companies, and to assess the selling prices of some prescription drugs, in order to portray a true picture of pharmaceutical pricing in Malaysia.…”
Section: Introductionmentioning
confidence: 99%